Phenibut (β-Phenyl-γ-aminobutyric Acid) Dependence and Management of Withdrawal: Emerging Nootropics of Abuse - Tania Ahuja; Ofole Mgbako; Caroline Katzman; Allison Grossman (Case Reports in Psychiatry)
This case report describes the development of withdrawal from phenibut, a gamma-aminobutyric acid-receptor type B agonist. Although phenibut is not an FDA-approved medication, it is available through online retailers as a nootropic supplement. There are reports of dependence in patients that misuse phenibut. We report a case in which a patient experienced withdrawal symptoms from phenibut and was successfully treated with a baclofen taper. This case report highlights the development of phenibut use disorder with coingestion of alcohol and potential management for phenibut withdrawal. We believe clinicians must be aware of how phenibut dependence may present and how to manage the withdrawal syndrome.